Investigating the Link Between Dalcroze Eurhythmics and Musical Expressivity in Novice Piano Students - Dalaire, Mélina (Université d'Ottawa / University of Ottawa, 2020)
The purpose of this study was to investigate the link between Dalcroze training and the improvement of musical expressivity in piano performance with a young population of novice piano students. This was tested by measuring variations in dynamics, timing and articulation, collected with MIDI data in a single-subject quasi-experimental design in which participants served as their own control. Data was collected from nine children either performing A Short Story (Lichner) or Lightly Row (folk song). During the pretest phase, the 9 participants performed their musical excerpt hands together and right hand only. Pretest 1 occurred one week before the intervention and Pretest 2 occurred immediately before the intervention. During the intervention phase, participants received three 60-minute Dalcroze lessons on three consecutive days by a certified and experienced Dalcroze teacher. During the posttest phase, participants performed the same excerpts under the same conditions as in the pretests. Posttest 1 occurred immediately after the 3rd Dalcroze lesson and Posttest 2 occurred 1 week after the intervention phase. Our initial hypothesis stated that evidence of an intervention effect on musical expressivity would be measurable after the Dalcroze lessons. We expected that some participants may perform some posttest phrases with audibly perceptible differences. Musical expressivity was considered “changed” if the posttest phrase arch showed a) larger differences than the pretest measurements and/or b) measurements would change from opposite than expected results in pretests to expected results in posttests. The results of the present study refute our hypothesis for all dynamics, timing and articulation analysis.
Keywords: Dalcroze; Piano Performance; Quantitative; Musical Expressivity; Measurement; Young Children